Effect of ultrasonic and infrared treatments on microbial population, physicochemical properties, and total phenols of sprouted wheat powder - samira Amin-Ekhlas; mohammadreza Pajohi-Alamoti; Fakhreddin Salehi (فناوری‌های جدید در صنعت غذا)
Sprouting is a simple technique for improving the nutritional and quality characteristics of cereal grains. The purpose of this work was to examine ultrasonic pretreatment and drying methods (hot-air and infrared) on microbial population (total bacterial counts, molds, and yeasts), physicochemical properties (ash content, moisture, acidity, pH, lightness, redness, and yellowness), and total phenolic content of sprouted wheat powder (SWP). The results confirmed that the sonication decreased the total bacterial count of SWP. In this work, drying sprouted wheat with the hot-air and infrared radiation killed all molds and yeasts in the powders, and no molds or yeasts grew on the microbial plates. Moisture content, redness, yellowness, and phenolic content of SWP dried by the infrared dryer were higher than those by the hot-air dryer. The acidity and lightness of SWP dried by the hot-air dryer were higher than those by the infrared dryer. Applying ultrasonic pretreatment to sprouted wheat increased the amount of phenolic compounds in the powders, but this increase was not significant (p>0.05). In general, ultrasonic pretreatment and the use of infrared dryers are promising techniques for production of SWP with high phenolic content and low microbial population.